Mud volcanoes in the Gulf of Mexico; a mechanism for mixing sediments of different ages in slope environments - Kohl, Barry; Roberts, Harry H. (Gulf Coast Association of Geological Societies Transactions, 1995)
The extrusion of older, unconsolidated sediments onto the seafloor during the Quaternary is one explanation for frequent occurrences of displaced fossil microfaunas encountered at depth in wells drilled on the flanks of salt diapirs in the continental slope environment. Samples from mud volcanoes on the Louisiana continental slope were collected in 1992 and 1993 for foraminiferal studies by using the Johnson Sea-Link I & II manned submersibles. Age dating by use of planktonic foraminifera has shown that sediments ranging in age from middle Miocene to Pleistocene are being deposited on the modern seafloor by active mud vents/volcanoes. These sediments, when buried by modern pelagic or more rapidly deposited terrigenous clastics, would be anomalous when encountered in coreholes or exploratory wells. Vents, as shown by seismic sections, are associated with faults which provide the connection to older subsurface fine-grained sediments that are: 1) mobilized by gas and fluids, 2) carried to the surface, and 3) ejected onto the seafloor to form mud volcanoes and fine-grained sediment flows. The mud volcanoes are in water depths ranging from 300 to 690 meters located in Garden Banks Block 382, Green Canyon Blocks 143 and 272, and Mississippi Canyon Block 929. This study is part of an ongoing investigation of the geology around cold vents which support chemosynthetic faunal communities in the Gulf of Mexico. These results have important implications for age dating subsurface sediments encountered in wells and coreholes on the continental slope.
id: 63